Anatomy of a crisis: The causes and consequences of surging food prices - Headey, Derek D.; Fan, Shenggen (International Food Policy Research Institute, 2008)
Although the potential causes and consequences of recent increases in international food prices have attracted widespread attention, many existing appraisals are superficial and/or piecemeal. This paper attempts to provide a more comprehensive review of these issues based on the best and most recent research, and includes fresh theoretical and empirical analysis. We first analyze the causes of the current crisis by considering how well standard explanations hold up against relevant economic theory and important stylized facts. Some explanations, especially rising oil prices, the depreciation of the US dollar, biofuel demand, and some commodity-specific explanations, hold up much better than some others. We then provide an appraisal of the likely macro- and microeconomic impacts of the crisis in developing countries. We observe a large gap in the effects of macro and micro factors, and note that when these factors are used to identify the most vulnerable countries, the results often point in different directions. We conclude with a brief discussion of what ought to be learned from this crisis.